Leadership development as a novel strategy to mitigate burnout among female physicians - Dawn M. Sears; Alexis Bejeck; Laurel Kilpatrick; Nicole Griggs; Lindsey Farmer; Brittany Jackson; Hania Janek; Anthony C. Waddimba (PLoS ONE, 2025)
Background Female physicians are more likely to experience burnout and less likely to hold leadership positions. Effective interventions are needed to support women physicians in the workforce. Objective To determine if a shared learning, social-based leadership development program will impact burnout and career trajectory for female physicians. Design Cohort study. Setting Multispecialty healthcare system and state medical society members. Participants Burnout and Engagement surveys were emailed to 5000 physicians within the Baylor Scott & White Health System (BSWH). The external control group consisted of 516 female physicians within the Texas Medical Association (TMA) and not associated with BSWH. Internal controls included both male (670) and female physicians (240) who did not participate in the program. Intervention The Women Leaders in Medicine (WLiM) program included twice-annual in person summits and support programs throughout the 2-year study period. Measurements The Maslach Burnout Index (MBI) was utilized to evaluate burnout. Surveys were conducted at three separate points and included interest in leadership, intent to retain current employment, and open comments. Results Participants in WLiM had decreased frequency of high emotional exhaustion (mean 2.9 decreased to 2.5), decreased occurrence of high depersonalization (mean 1.6 decreased to 1.3), and improved levels of personal accomplishment (mean 4.7 improved to 5.1) and leadership aspiration (mean 7.4 to 7.8). Intention to stay went from 4.0 to 4.1. Conclusions Burnout can be improved, and leadership aspirations fostered with a group leadership development in a cohort of female physicians.